Study of the Santal-Psychiatric Patients and their Belief Towards Mental Illness (TAJ: Journal of Teachers Association, 2018)
This study aims at finding the presence of psychiatric illness of the santals, an ethnic minorities of the northern part of Bangladesh and their belief towards mental illness. Among the 77 patients, 39 (50.64%) were male and 38 (49.35%) were female. The majority of the respondents were in between the age of 16-35 years. Most (80%) believed that possession by Bonga/Kali caused the illness. In the present study, 45 (59.74%) had major mental disorder, 18 (23.37%) had minor mental disorders and 13 (16.88%) had psychotic disorder due to general medical condition (viz. Epilepsy). Observations suggest that change of awareness and perception regarding mental disorder, should be a high priority, as right mental health is one of the key component of total delivery of health care.TAJ 2011; 24(2): 76-81